Vocational and professional guidance as an alternative in the choice of university careers - Dillon-Pérez, Francisco (2023)
Vocational and professional orientation processes should allow high school students to select a university career oriented to their life project. However, many students drop out in the first semesters of college due to various factors (economic, emotional, psycho-pedagogical, among others). Among these is also the lack of professional orientation and the construction of vocational and professional tasks that consolidate this career choice. The objective of this research work was to determine the influence of the professional orientation process on the choice of university careers in third year high school students. The approach used was quantitative of an explanatory and correlational type supported by a qualitative analysis process of an interpretative hermeneutic type. The study population was selected through a purposive sampling and consisted of 342 students in the third year of high school from various public and private educational institutions in Ecuador. A battery of tests of professional aptitudes and interests and a structured interview were used as research instruments. The results of the statistical study carried out have made it possible to identify the influence of professional orientation on the choice of a university career in the study population. It is therefore concluded that this process could help students in this context to choose a career aligned with their life project and aptitudinal potential.